2012
DOI: 10.1177/1477370812454204
|View full text |Cite
|
Sign up to set email alerts
|

Victimology in transitional justice: Victimhood, innocence and hierarchy

Abstract: Although addressing the needs of victims is increasingly proffered as the key rationale for transitional justice, serious critical discussion on the political and social construction of victimhood is only tentatively emerging in the field. Drawing from Anglo-American victimology, the first part of this paper suggests that victims of crime as a category are often perceived as the mirror opposite of perpetrators of crime. It suggests that such a perspective narrows the notion of victims’ rights or needs so they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 38 publications
(18 reference statements)
0
94
0
Order By: Relevance
“…Victimcentric discourses have underpinned the contemporary regulatory regime with the co-optation of the crime victim providing 'an all-purpose justification for measures of penal repression' (Garland, 2001: 143) and a whole industry of 'offender-focused corrections ' (McEvoy andMcConnachie, 2012: 530, citing Rock, 1998). Other scholars have explored what has been termed 'the politics of victimhood' (Bouris, 2007: 10) within the context of peace making or transitional justice (McEvoy and McConnachie, 2012). This article extends this discussion by examining the construction and reproduction of victimhood, as well as offending behaviour, within the context of risk-centric discourses concerning sex offending against children.…”
Section: Introductionmentioning
confidence: 89%
“…Victimcentric discourses have underpinned the contemporary regulatory regime with the co-optation of the crime victim providing 'an all-purpose justification for measures of penal repression' (Garland, 2001: 143) and a whole industry of 'offender-focused corrections ' (McEvoy andMcConnachie, 2012: 530, citing Rock, 1998). Other scholars have explored what has been termed 'the politics of victimhood' (Bouris, 2007: 10) within the context of peace making or transitional justice (McEvoy and McConnachie, 2012). This article extends this discussion by examining the construction and reproduction of victimhood, as well as offending behaviour, within the context of risk-centric discourses concerning sex offending against children.…”
Section: Introductionmentioning
confidence: 89%
“…The question of the innocence of victims was never raised. Particularly for the 28 victims of the London bombings, there was a sense that public empathy was high. Perhaps due to the random nature of their experience, it resonated with all Londoners who took a daily commute.…”
Section: Discussionmentioning
confidence: 99%
“…The use of biased language relates to the notion of the 'deserving victim', a concept that has been widely debated within victimology literature. Researchers have observed that a hierarchy exists among victims, where some individuals are viewed as deserving of victim status and others are viewed as being responsible for their experiences (McEvoy & McConnachie, 2012). In historical victimological theory and research, some victims were classified in the hierarchy based on how much they were perceived to have contributed to, or caused, their own victimisation.…”
Section: The Use Of Languagementioning
confidence: 99%
“…In historical victimological theory and research, some victims were classified in the hierarchy based on how much they were perceived to have contributed to, or caused, their own victimisation. This was termed 'precipitation', where victims are viewed as having contributed to their experiences and, consequently, blame is assigned to them, whereas others are viewed as innocent (McEvoy & McConnachie, 2012). This debate extends to victims of sexual abuse, where it is argued that an 'ideal victim' is vulnerable, that they should appear to others as being powerless in the encounter and that they are dominated by the perpetrator.…”
Section: The Use Of Languagementioning
confidence: 99%